Gender and science: characterization of productivity researchers at UFAL (Seminário Internacional de Informação, Tecnologia e Inovação, 2024)
This study addresses the presence and representation of women in recognition and leadership systems in scientific fields present at the Federal University of Alagoas. The objective is to characterize the female presence of productivity researchers from the National Council for Scientific and Technological Development at the Federal University of Alagoas. The research can be characterized as exploratory, with a quantitative and qualitative perspective in which documentary research was used, using categorization for analytical comparisons. The study contributes to the understanding of gender inequality and reinforces the importance of feminism in promoting equity in science.
Keywords: gender inequality; scientific production; feminism; productivity scholarship